2019
DOI: 10.1002/jso.25503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of race and geographic setting on the management of gastric adenocarcinoma

Abstract: Background and Objectives Conflicting evidence indicates that both race and geographic setting may influence the management of malignancies such as gastric adenocarcinoma (GAC). Methods We designed a retrospective cohort study utilizing data from the Surveillance, Epidemiology, and End Results program to identify patients with resectable GAC (N = 15 991). Exposures of interest were race and geographic region of diagnosis (West [WE], Midwest [MW], South [SO], or Northeast [NE]). Endpoints included: (1) recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…Another possibility is that disparities may exist in management practices. Studies have shown that race and geographic region of diagnosis impact treatment recommendations and gastric adenocarcinoma‐specific survival among individuals with resectable tumors 36 . For example, blacks with resectable gastric tumors are more likely to receive a recommendation against surgery than individuals of other racial groups 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that disparities may exist in management practices. Studies have shown that race and geographic region of diagnosis impact treatment recommendations and gastric adenocarcinoma‐specific survival among individuals with resectable tumors 36 . For example, blacks with resectable gastric tumors are more likely to receive a recommendation against surgery than individuals of other racial groups 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that race and geographic region of diagnosis impact treatment recommendations and gastric adenocarcinoma‐specific survival among individuals with resectable tumors 36 . For example, blacks with resectable gastric tumors are more likely to receive a recommendation against surgery than individuals of other racial groups 36 . Zhang et al noted significant differences between racial and ethnic groups in the treatment of gastric cancer across stages, with Asians/Pacific Islanders having the highest rate of surgery plus radiation 10 …”
Section: Discussionmentioning
confidence: 99%
“…24 It has been postulated that these health care disparities can be attributed to various factors that affect the African American community, including limited access to health care, distrust of the medical establishment, and implicit bias. 13 Our investigation revealed several compelling findings that contribute to the ongoing discussion on race and health care Figure 2. Panel A. predicted probability of intervention based on race.…”
Section: The Effect Of Race On Hcc Management and Outcomesmentioning
confidence: 80%
“…African Americans with resectable gastric cancer, for example, are more likely to receive a recommendation against surgery than their White and Asian counterparts. 13 The female sex favors prolonged survival in numerous malignancies, including head and neck cancers, melanoma, and leukemia. 14 Low income individuals tend to fare substantially worse than the wealthy across a range of health-related outcomes, including quality of life and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there might be other factors that are more speci c to individual types of gastrointestinal cancers. For example, esophageal adenocarcinoma is more frequent among non-Hispanic whites (NHW); esophageal squamous cell carcinoma and colorectal cancer are more frequent among African Americans and the reasons might be multifactorial, including socioeconomic and lack of health care access, treatment, and prevention [4][5][6][7][8][9]. Also, a lower rate of surgery among Hispanics for esophageal cancer was associated with a decreased survival rate when compared to whites, even when adjusted for relevant socioeconomic and tumor factors [10].…”
Section: Introductionmentioning
confidence: 99%